Causes of feeding frequency on feeding efficiency, growth and economic feasibility of rearing African catfish (Clarias gariepinus) juveniles and fingerlings - Victor Sebastian; George Davison; Lebechi (Advances in Aquaculture and Fisheries Management, 2014)
Feeding frequency effect on growth performance, feed utilization and economic viability of Clarias gariepinus fingerlings and juveniles were studied under natural photoperiods of 12/12 h light/dark cycle using a complete random design. Triplicate group of 10 fish with an initial mean weight of 8.5 ± 0.1 g and 34.3 ± 0.1 g respectively per tank (measuring 52 x 33.5 x 21 cm). A commercial feed (COPPENS) with crude protein of 42% and ether extract 12% was fed for 8 weeks over four feeding frequencies studied (once, twice, thrice and four times). Mean weight gain, relative growth rate and the specific growth rate were all significantly different (P < 0.05) across feeding levels except at thrice and four times feeding levels. The feed conversion ratio was lowest on three times a day feeding level both for the juvenile and fingerling (0.66 and 0.73, respectively). Although net profit value, in both juvenile and fingerling group are not significantly different, the investment cost analysis and the gross profit between fish fed thrice and four times are equally not significantly (P > 0.05) different. The results of this experiment, both at the juvenile and fingerling stages indicate that fish could be fed three times a day with maximum growth and profit.